Effects of Climate Warming, North Atlantic Oscillation, and El Niño-Southern Oscillation on Thermal Conditions and Plankton Dynamics in Northern Hemispheric Lakes. (2002) - Gerten, Dieter; Adrian, Rita
Abstract : Impacts of climate warming on freshwater ecosystems have been documented recently for a variety of sites around the globe. Here we provide a review of studies that report long-term (multidecadal) effects of warming trends on thermal properties and plankton dynamics in northern hemispheric lakes. We show that higher lake temperatures, shorter periods with ice cover, and shorter stagnation periods were common trends for lakes across the hemisphere in response to the warmer conditions. Only for shallow dimictic lakes was it observed that deep-water temperatures decreased. Moreover, it became evident that phytoplankton dynamics and primary productivity altered in conjunction with changes in lake physics. Algal spring blooms developed early and were more pronounced in several European lakes after mild winters with short ice cover periods, and primary productivity increased in North American lakes. Effects of elevated temperatures on zooplankton communities were seen in an early development of various species and groups, as is documented for cladocerans, copepods, and rotifers in European lakes. Furthermore, thermophile species reached higher abundance in warmer years. Obviously, the nature of responses is species specific, and depends on the detailed seasonal patterning of warming. Complex responses such as effects propagating across trophic levels are likely, indicating that observed climate—ecosystem relationships are not generally applicable. Nonetheless, the picture emerges that climate-driven changes in freshwater ecosystems may be synchronised to a certain extent among lakes even over great distances if climatic influences are not masked by anthropogenic impacts or differences in lake morphology. Macro-scale climatic fluctuations — such as the North Atlantic Oscillation or the El Niño-Southern Oscillation — were identified as the most important candidates responsible for such coherence, with the former predominating in Europe and the latter in North America. We emphasise, however, that the driving mechanisms and the future behaviour of these oscillations are rather uncertain, which complicates extrapolation of observed effects into the future. Thus, it is necessary to quantify the most important climate—ecosystem relationships in models of appropriate complexity. Such models will help elucidate the multiple pathways climate affects freshwater ecosystems, and will indicate possible adverse effects of a warmer future climate.